Handbook on the historical books Joshua, Judges, Ruth, Samuel, Kings, Chronicles, Ezra-Nehemiah, Esther - Hamilton, Victor P. (Grand Rapids, MI Baker Academic, 2001)
Includes bibliographical references and index.
Keywords: Bible. O.T. Historical Books -- criticism, interpretation, etc